Implementation Of The Group Investigation Model To Improve Learning Outcomes Of 6th Grade Students On Islamic Cultural History Material At MI PSM Gedoro - Nur Fatimah Azzahra; Nabila Khoyrun Nisa; Eka Hidayatin (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
Islamic Cultural History lessons at MI PSM Gedoro often face challenges in increasing student engagement due to being perceived as boring. To address this issue, this study applies the